Alteplase for Acute Ischemic Stroke: Outcomes by Clinically Important Subgroups in the Third International Stroke Trial. Issue 3 (March 2015) - Lindley, Richard I.; Wardlaw, Joanna M.; Whiteley, William N.; Cohen, Geoff; Blackwell, Lisa; Murray, Gordon D.; Sandercock, Peter A.G.; Baigent, Colin; Chadwick, David; Tyrrell, Pippa; Lowe, Gordon; Dennis, Martin; et al.
Abstract : Background and Purpose—: Our aim was to identify whether particular subgroups of patients had an unacceptably high risk of symptomatic intracranial hemorrhage or low chance of benefit when treated with alteplase (recombinant tissue-type plasminogen activator). Methods—: Third International Stroke Trial was an international randomized trial of the intravenous (IV) recombinant plasminogen activator alteplase (0.9 mg/kg) versus control in 3035 (1515 versus 1520) patients. We analyzed the effect of recombinant tissue-type plasminogen activator on 6-month functional outcome, early death, and symptomatic intracranial hemorrhage (both ⩽7 days). We tested for any differences in treatment effect between subgroups by a test of interaction. Our 13 protocol prespecified subgroups were time to randomization, age, sex, stroke subtype, atrial fibrillation, early ischemic change (clinician and expert panel), prior antiplatelet use, stroke severity, diastolic and systolic blood pressure at randomization, center's thrombolysis experience, and trial phase. Analyses were adjusted for key baseline prognostic factors. Results—: There were no significant interactions in the subgroups analyzed that were consistent across all 3 outcomes. Treatment with recombinant tissue-type plasminogen activator increased the odds of symptomatic intracranial hemorrhage by a greater amount in patients taking prior antiplatelets than those who were not ( P =0.019 for test of interaction), but had no clear detrimental effect on functional outcome at 6 months in this group ( P =0.781 for test of interaction). Conclusions—: Among the types of patient in the Third International Stroke Trial, this secondary analysis did not identify any subgroups for whom treatment should be avoided. Given the limitations of the analysis, we found no clear evidence to avoid treatment in patients with prior ischemic stroke, diabetes mellitus, or hypertension. Clinical Trial Registration—: URL:http://www.controlled-trials.com . Unique identifier: ISRCTN25765518.http://www.controlled-trials.com/ISRCTN25765518 .